On Repeated Games with Imperfect Public Monitoring: From Discrete to Continuous Time - Mathias Staudigl; Jan-Henrik Steg (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
Motivated by recent path-breaking contributions in the theory of repeated games in continuous time, this paper presents a family of discrete-time games which provides a consistent discrete-time approximation of the continuous-time limit game. Using probabilistic arguments, we prove that continuous-time games can be defined as the limit of a sequence of discrete-time games. Our convergence analysis reveals various intricacies of continuous-time games. First, we demonstrate the importance of correlated strategies in continuous-time. Second, we attach a precise meaning to the statement that a sequence of discrete-time games can be used to approximate a continuous-time game.
Keywords: 330; continuous-time game theory; stochastic optimal control; weak convergence